2021
DOI: 10.1177/10775463211038830
|View full text |Cite
|
Sign up to set email alerts
|

Raft attitude control and elastic deformation suppression technique for large-scale floating raft air spring mounting system

Abstract: The structure of floating rafts-equipped vessels will be inevitably undermined due to application of large-scale designs. When encountering strong external disturbances, not only the rafts will deviate from the original balanced position but also greater elastic deformation will be generated, which may lead to the relative displacement between devices on rafts and endanger the operation safety of equipment. In this study, a class of raft elastic deformation monitoring and discrimination methods is put forward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Floating raft ship structure encountered external disturbances, it is easier to produce elastic deformation. Consequently, Qiu et al [9] established a flexible raft control response model based on the finite element, and its pressure parameters to identify to inhibit its elastic deformation results. The results showed that the method can effectively improve the control accuracy of the raft plate and reduce the deformation.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Floating raft ship structure encountered external disturbances, it is easier to produce elastic deformation. Consequently, Qiu et al [9] established a flexible raft control response model based on the finite element, and its pressure parameters to identify to inhibit its elastic deformation results. The results showed that the method can effectively improve the control accuracy of the raft plate and reduce the deformation.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Te size and weight of FR have further increased, reaching tens of meters and hundreds of tons [12]. It is difcult to optimize the FR due to various practical constrains.…”
Section: Potential Lightweight Technologies and Its Applicationsmentioning
confidence: 99%
“…Thus, it is necessary to monitor and predict the alignment state in real time, and carry out precise alignment control by actively adjusting the air spring pressure. However, in large-scale ASVISs, due to factors such as strong interference and raft deformation, alignment prediction faces problems such as alignment measurement sensors failure and difficulty in establishing a mathematical model [5,6], making alignment prediction a challenging problem.…”
Section: Introductionmentioning
confidence: 99%